INTRANET INFORMATION IN DRUG SALES DATA USING FOXPRO 2.6 - Agus Susanto; Ristyawati Ristyawati, S.Kom., MMSI (Jurnal Sistem Informasi, 2004)
This explains the scientific writing about the design of the Intranet programs in drugsales information by using a programming language FoxPro 2.6 and assistanceprograms that ACCPAC PLUS program package. In this scientific writing, to knowthe sales results from both the Daily sales per Pharmacies and per product is still a lotof manual rendering them ineffective and inefficient, therefore, to overcome thisauthor tries to provide information daily sales data by utilizing computerized Intranetfacilities. At the end sales of the drug application programs using the Intranet facilityas this information will be applied to the PT. Gala Djaja Kingdom to facilitate inproviding information and creating reports.